HUMANISME SEKULAR DALAM IFIGENIA DI SEMENANJUNG TAURIS KARYA J. V. GOETHE - Mateus Rudi Supsiadji (Universitas 17 Agustus 1945 Surabaya, 2013)
Abstract. This article reports an investigation of secular humanism values in J.V. Goetheâ€™s Ifigenia di Semenanjung Tauris. The issues being investigated are: (1) the conflicts among the characters, and (2) the values of secular humanism in the conflicts themselves. This study adopts the theory of humanism that is the system of belief based on a faith in democracy, rationality, and human autonomy. The research uses descriptive qualitative method in which the data are in the form of text. The analysis shows that the conflicts are caused by personal will based on authority, religion, and revenge, and the rejection of the will based on humanity. Agamemnon and Thoas represent the authority to fulfill their will of human sacrifice in accordance with their religious teaching. On the contrary, Ifigenia represents the rejection of human sacrifice. The debate between the fulfillment of the will and the rejection of the will reveals the values of humanism.Â Key words: conflict, humanism secular, human autonomy